Short-term stimulation of net glycogen production by insulin in rat hepatocytes - Nyfeler, Fritz; Fasel, Paul; Walter, Paul (Biochimica et biophysica acta, 1981)
Isolated liver cells from 24 h starved rats were incubated in Krebs-Ringer buffer containing 4% albumin. In the presence of 10, 20 and 30 mM glucose, addition of insulin stimulated net glycogen production by 52, 39 and 20%, respectively. 2 · 10 −9 M insulin was required for half-maximal stimulation. Increases of glycogen production and of glycogen synthase a activity were observed after 15–30 min of incubation with insulin. The stimulatory effect of insulin was additive to that of lithium. In agreement with the literature, insulin antagonized the inhibitory action of suboptimal doses of glucagon on glycogen deposition whereby a decrease of glucagon-elevated cyclic AMP levels was observed. In addition, we found that insulin also decreased the basal cyclic AMP levels in the absence of added glucagon by 22%. It is concluded that physiological concentrations of insulin stimulate net glycogen deposition in hepatocytes from fasted rats; the decrease of basal cyclic AMP levels upon insulin addition may play a role in the mechanism of the hormone action.